Development Of A Real-Time Pcr Assay For Diagnosis Of Brucella Melitensis Infection In Sheep - Belay, Takele (2008)

(untitled)
In this study, a SYBR Green based real-time PCR assay using primers specific to IS711 of Brucella melitensis was developed and its diagnostic utility was evaluated by comparing it with conventional PCR method for detection of Brucella DNA from cultured bacteria and experimentally infected mice samples. The study was first undertaken with cultured bacteria, B. melitensis 16M as a reference and two B. melitensis Malysian isolates. Brucella abortus 544 and Yersinia enterocolitica O:9 were also used for cross reactivity testing. Three of the B. melitensis were successfully detected using both optimized SYBR Green I real-time and conventional PCR. No amplification products were produced with these primers from strains of B. abortus and Y. enterocolitica O:9 indicating that the primer sets are specific only for B. melitensis. The specificity of the PCR products amplified by the primers from Malysian strains of B. melitensis were confirmed by sequence analysis. The detection limit of the real-time PCR was compared with conventional PCR by preparing serially ten-fold dilutions of B.melitensis DNA. The real-time PCR was found to be 10-fold more sensitive than the conventional PCR, detecting up to 50 fg of genomic DNA. The viability of using conventional and real-time PCR assays together with culture methods as potential diagnostic tools for the detection of B. melitensis in experimentally infected mice was also assessed over an 8-week period of infection. It was evident from our result that regardless of duration of infection and sample type (liver, lymph node, blood, spleen and serum) the diagnostic yield (sensitivity) was 100%, 96.7% and 62.5% for real-time PCR, conventional PCR and culture methods respectively. This indicated that the sensitivity of the PCR assays was far higher than that of the culture method. The specificity of both conventional and real-time PCR was 100%. When serum was used as PCR template, B. melitensis specific amplicon was detected only until day 45 post inoculation (p.i) using conventional PCR unlike the real-time PCR method whereby positive results were detected through out the study period. In all samples with positive real-time PCR results, B. melitensis specific amplicons were distinguished by their characteristic melting temperature ranged between 86.4 oC to 87.4 oC in melting curve analysis. Analytical sensitivities of the different tissue types used in the study were also compared using threshold cycle (Ct) values of the real-time PCR. For this purpose, samples collected at day 30 p.i. were used and the most sensitive tissue sample amongst the tested samples was estimated from the standard curve obtained from cloned B. melitensis 16M. Accordingly, the most sensitive tissue was found to be serum (mean Ct=15.07) followed by lymph node (mean Ct=19.50), spleen (mean Ct= 24.2), liver (mean Ct=26.4) and whole blood (mean Ct=26.2). These results indicate that serum samples followed by lymph node are more sensitive for the real-time PCR assay than the other samples tested in this study. In conclusion, this present results suggest that the diagnostic yield of real-time PCR that uses serum samples was at least as sensitive as a similar PCR protocol that uses other tested tissue samples. The speed and technical simplicity of real-time PCR coupled with minimal risk of handling serum samples make it a useful alternative to blood / other tested tissue PCR for animals with suspected brucellosis and negative or doubtful serological test results. However, although the use of this real-time PCR assay as a supplemental diagnostic tool for detection and identification of Brucella organisms in clinical specimens could be recommended, the need for the assay to be validated with confirmed positive and negative clinical samples of its primary host animals, and verify its ability to differentiate the vaccinal strains from field strains, is desirable to achieve the utmost benefits from the SYBR Green I based real-time PCR assay.